Durable all-inorganic perovskite tandem photovoltaics - Duan, Chenghao; Zhang, Kaicheng; Peng, Zijian; Li, Shiang; Zou, Feilin; Wang, Feng; Li, Jiong; Zhang, Zheng; Chen, Chang; Zhu, Qiliang; Qiu, Jianhang; Lu, Xinhui; et al. (Nature, 2025)
All-inorganic perovskites prepared by substituting the organic cations (for example, methylammonium and formamidinium) with inorganic cations (for example, Cs+) are effective concepts to enhance the long-term photostability and thermal stability of perovskite solar cells (PSCs)1,2. Hence, inorganic perovskite tandem solar cells (IPTSCs) are promising candidates for breaking the efficiency bottleneck and addressing the stability issue, too3,4. However, challenges remain in fabricating two-terminal (2T) IPTSCs due to the inferior film formation and deep trap states induced by tin cations5-7. Here a ligand evolution (LE) strategy with p-toluenesulfonyl hydrazide (PTSH) is used to regulate film formation and eliminate deep traps in inorganic narrow-bandgap (NBG) perovskites, enabling the successful development of 2T IPTSCs. Accordingly, the 1.31 eV CsPb0.4Sn0.6I3:LE device delivers a record efficiency of 17.41%. Combined with the 1.92 eV CsPbI2Br top cell, 2T IPTSCs exhibit a champion efficiency of 22.57% (certified, 21.92%). Moreover, IPTSCs are engineered to deliver remarkable durability under maximum power point (MPP) tracking, maintaining 80% of their initial efficiency at 65 °C for 1,510 h and at 85 °C for 800 h. We elucidate that LE deliberately leverages multiple roles for inorganic NBG perovskite growth and anticipate that our study provides an insightful guideline for developing high-efficiency and stable IPTSCs.
CRIS-Team Scopus Importer:2025-02-17